Regional cultures of Ukraine and perceptions of poverty = Kultury regionalne Ukrainy a postrzeganie ubóstwa - Pohorila, Nataliia (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper presents pondering on the perception of poverty. Tries to explain when and why people blame the poor for their laziness and the lack of willpower. Interregional variation in the individual blame is explained from the point of view of economic development and local/regional culture. State paternalism, materialism and xenophobia are analysed as the cultural constructs that may influence the popular perception of poverty as a poor`s fault - the interregional difference in the individual blame in Ukraine. The data for analysis are taken from the European Value Survey, 2008.
Keywords: poverty; individual blame; social blame; regional culture; ubóstwo; wina jednostki; wina społeczna; kultura regionalna